2021
DOI: 10.1021/acsanm.1c01954
|View full text |Cite
|
Sign up to set email alerts
|

Pt and ZnFe2O4 Nanoparticles Immobilized on Carbon for the Detection of Glutathione

Abstract: The catalytic activity of nanozymes has attracted much attention in biochemical analyses and the antibiosis and environmental fields. However, easy aggregation and difficulty in recycling greatly result in a decrease of their catalytic activity and further restrict their practical application. Herein, we immobilized Pt and ZnFe 2 O 4 nanoparticles on poplar-wood-derived carbon (ZnFe 2 O 4 /C), which exhibited excellent peroxidase-like activity and high affinity toward H 2 O 2 and 3,3′,5,5′-tetramethylbenzidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Furthermore, compared with CoGa 2 O 4 , the peak position of O1s attributed to lattice oxygen in the Co 0.65 Zn 0.35 Ga 1.3 Fe 0.7 O 4 solid solution shifts toward lower binding energy (Figure 3f). The O1s peak of the solid solution corresponds to the lattice oxygen binding energy of 530.20 eV, which is higher than that of ZnFe 2 O 4 (530.09 eV), indicating the presence of new bonds [27–29] . In summary, the prepared Co 0.65 Zn 0.35 Ga 1.3 Fe 0.7 O 4 is a solid solution of cubic CoGa 2 O 4 and cubic ZnFe 2 O 4.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, compared with CoGa 2 O 4 , the peak position of O1s attributed to lattice oxygen in the Co 0.65 Zn 0.35 Ga 1.3 Fe 0.7 O 4 solid solution shifts toward lower binding energy (Figure 3f). The O1s peak of the solid solution corresponds to the lattice oxygen binding energy of 530.20 eV, which is higher than that of ZnFe 2 O 4 (530.09 eV), indicating the presence of new bonds [27–29] . In summary, the prepared Co 0.65 Zn 0.35 Ga 1.3 Fe 0.7 O 4 is a solid solution of cubic CoGa 2 O 4 and cubic ZnFe 2 O 4.…”
Section: Resultsmentioning
confidence: 82%
“…The O1s peak of the solid solution corresponds to the lattice oxygen binding energy of 530.20 eV, which is higher than that of ZnFe 2 O 4 (530.09 eV), indicating the presence of new bonds. [27][28][29] In summary, the prepared x Zn x Fe 2x Ga 2-2x O 4 (0 < x � 0.6) solid solution samples. In Figure 4a, all samples were evaluated for photocatalytic activity, and carbon dioxide photoreduction experiments were performed without the addition of cocatalyst, sacrificial agent, or photosensitizer.…”
Section: Resultsmentioning
confidence: 93%
“…Fe 0.027 Sn 0.973 S 2 shows ferromagnetic behaviour at 300 K. Srivind et al have reported weak ferromagnetic behaviour for iron doped SnS 2 nanopowders ([Fe] = 0 to 15%) at room temperature. [45] Many reports are available in literature on the peroxidaselike activity using magnetic nanoparticles such as Fe 3 O 4 , [67,68] Co 3 O 4 @BSA, [69] Pt and ZnFe 2 O 4 nanoparticles immobilized on carbon, [70] ABEI functionalized CuFe 2 O 4 , [71] and Fe nanoparticles [72] as the catalyst. The authors have demonstrated that these magnetic nanoparticles can be separated using an external magnet after the catalytic reaction.…”
Section: Mechanism Of Formation Of Sn 1-x Fe X S 2 Nanoparticlesmentioning
confidence: 99%
“…Various magnetic spinel nanoparticles have been reported in literature for the peroxidase-like activity including Pt and ZnFe 2 O 4 nanoparticles immobilized on carbon, [82] ABEI functionalized CuFe 2 O 4 , [83] and Fe 3 O 4 nanoparticles. [84] In the current study, after the catalytic reaction, an external magnet was used for the separation of catalyst.…”
Section: Recyclability Studiesmentioning
confidence: 99%